THE EFFECT OF MOISTURE ON THE PHYSICAL CHARACTERISTICS OF RANITIDINE HYDROCHLORIDE TABLETS PREPARED BY DIFFERENT BINDERS AND TECHNIQUES - (:unkn) unknown (MARCEL DEKKER INC, 1991)
The effect of moisture on the physical properties of ranitidine hydrochloride tablets prepared by direct-compression and by wet-granulation method using PVP or EC as binders was studied. Tablets adsorped moisture at 50 and 75 % RH (relative humidity) but lost moisture at 30% RH. Except storage at 75% RH, however, tablet volumes did not change significantly during the test period. Moisture sorption caused a decrease in strength of tablets except low humidity (30% RH). Also, the disintegration time of tablets showed a decrease at all conditions except 30% RH. Furthermore, generally dissolution profiles of tablets prepared by direct-compression and by ethyl cellulose remained unchanged. Changes in the binder type in the tablet formulations changed the water uptake properties and also the physical properties of tablets. Directly-compressed tablets were much susceptible to change caused by humidity than tablets prepared by wet-granulation.